Tinjauan Antropologi Hukum dan Budaya terhadap Mudik Lebaran Masyarakat Yogyakarta - Suud Sarim Karimullah (Lembaga penelitian dan pengabdian kepada Masyarakat, 2021)
The focus of this study lies on how the Islamic concept sees the phenomenon of the Eid homecoming?, and how is the legal and cultural anthropological review of the Yogyakarta society Eid homecoming?. Seeing and understanding in depth about the concept of Islam and a review of legal and cultural anthropology used as an analysis knife of the Eid homecoming phenomenon is the purpose of writing this article. While this research is a qualitative research by looking at the cultural value orientation in the Yogyakarta society. Then, the methods used to collect data are observation, interviews, and data collection through analysis of studies of various literature that have relevance to the study to be carried out with analytical descriptive properties through analysis of the Huberman and Miles model. Therefore, the results of the study show that the Eid homecoming carried out by the Yogyakarta society is one of the social actions or activities in culture that fall into the general category, namely